RVSNUpy: A Python Package for Spectroscopic Redshift Measurement Based on Cross Correlation - Taewan Kim; Jubee Sohn; Ho Seong Hwang (The Astronomical Journal)
We introduce RVSNUpy , a new Python package designed to measure spectroscopic redshifts. Based on inverse-variance-weighted cross correlation, RVSNUpy determines redshifts by comparing observed spectra with various rest-frame template spectra. We test the performance of RVSNUpy based on ∼6000 objects in the HectoMAP redshift survey observed with both the Sloan Digital Sky Survey (SDSS) and MMT/Hectospec. We demonstrate that a slight redshift offset (∼40 km s ^−1 ) between the SDSS and MMT/Hectospec measurements reported from previous studies results from the small offsets in the redshift template spectra used for SDSS and Hectospec reductions. We construct a universal set of template spectra, including empirical SDSS template spectra, carefully calibrated to the rest frame. Our test for the HectoMAP objects with duplicated observations shows that RVSNUpy with the universal template spectra yields homogeneous redshifts for spectra obtained with different spectrographs. We highlight that RVSNUpy is a powerful redshift measurement tool for current and future large-scale spectroscopy surveys, including A-SPEC, DESI, 4MOST, and the Subaru Prime Focus Spectrograph.